Neonatal Outcomes for Women at Risk of Preterm Delivery Given Half Dose Versus Full Dose of Antenatal Betamethasone: A Randomized, Multicentre, Double-blind, Placebo-Controlled, Non-inferiority Trial. Issue 2 (February 2023) - Schmitz, Thomas; Doret-Dion, Muriel; Sentilhes, Loic; Parant, Olivier; Claris, Olivier; Renesme, Laurent; Abbal, Julie; Girault, Aude; Torchin, Héloïse; Houllier, Marie; Le Saché, Nolwenn; Vivanti, Alexandre J.; et al.
ABSTRACT: Antenatal corticosteroid administration to women at risk of preterm delivery is recommended worldwide because of their effectiveness in preventing respiratory distress syndrome, as well as in reducing the rate of necrotizing enterocolitis, intraventricular hemorrhage, and neonatal death in preterm infants. However, the current usual dosage regimen of 2 injections of 12 mg of betamethasone (BMZ) 24 hours apart originated from preclinical experiments in the 1960s and has not been investigated in randomized clinical trials. These authors therefore designed a randomized trial for investigating whether a half dose of BMZ would be as effective as the standard full-dose regimen. The primary outcome was the need for exogenous surfactant within the first 48 hours of life. Secondary outcomes included the incidence and severity of respiratory disease, such as respiratory distress syndrome. This randomized, multicenter, double-blind placebo-controlled, noninferiority study was conducted in 37 perinatal centers in France. Pregnant women 18 years or older with singleton pregnancies at risk of delivery preterm (and already treated with dose 1 of antenatal BMZ before 32 weeks' gestation) were eligible to participate. Exclusion criteria included multiple pregnancy, having previously received full-dose antenatal corticosteroids, 4 cm or greater cervical dilation, cervical length of 20 mm or greater, fetal major malformations or chromosomal aberrations, or being unable to communicate fluently in French. Upon hospital admission after the first BMZ injection, women were provided information about the trial, and those who agreed were randomly assigned in a 1:1 ratio to receive either a saline placebo or the second intramuscular BMZ dose. A total of 3196 women participated, with 1597 in the half-dose group and 1599 in the full-dose group. In all, 30 fetuses were stillborn, 16 neonates were lost to follow-up, and 9 neonates died before evaluation, leaving 1567 neonates in the half-dose group and 1574 neonates in the full-dose group. In the intention-to-treat analysis, the primary outcome occurred in 313 (20%) of neonates in the half-dose group and 276 (17.5%) in the full-dose group (risk difference, 2.4%; 95% confidence interval [CI], 0.3–5.2); thus, noninferiority was not shown. The per-protocol analysis also did not show noninferiority (risk difference, 2.2%; 95% CI, −0.6 to 5.1). There were no differences in the rates of neonatal death, grade 3 to 4 intraventricular hemorrhage, stage ≥2 necrotizing enterocolitis, severe retinopathy of prematurity, or bronchopulmonary dysplasia. Between the 2 groups, all other secondary prematurity-associated outcomes were also similar. Strengths of the study included its large sample size and low loss-to-follow-up rate (0.5%), as well as consistent perinatal management approach through the Groupe de Recherche en Obstetrique et Gynecologie. However, the study also had limitations, such as the potential for the primary outcome to be considered a short-term surrogate only partially reflecting the overall severity of neonatal illness. The rate of the primary outcome observed in the study was also 2.5% lower than anticipated, which the authors attribute to the numbers of deliveries that occurred before 32 weeks' gestation and beyond 7 days following treatment. The number of births occurring within this window of time may limit the ability to demonstrate true differences between the 2 groups, meaning that the authors could not rule out the possibility of half-doses being inferior given higher preterm birth rates. In addition, long-term evaluation of the infants involved in the study via a follow-up evaluation at 5 years of age will be critical to determining the overall effect of BMZ dose reduction on neurological development. The authors concluded that this trial indicated the half-dose antenatal BMZ regimen did not meet criterion for noninferiority when compared with the currently recommended regimen in singleton pregnancies for preventing respiratory distress syndrome that requires exogenous intratracheal surfactant.